Photocatalytic Degradation of Diazinon in g-C3N4/Fe(III)/Persulfate System under Visible LED Light Irradiation - Rubi, Rugi Vicente C.; Olay, Jerry G.; Caleon, Paula Bianca G.; De Jesus, Rose Ann F.; Indab, Mikee Bernadette L.; Jacinto, Ryan Christian H.; Sabalones, McHill S.; Rosa, Francis dela; Hamidah, Nur Laila (Applied Science and Engineering Progress, 2021)
In the past years, the non-conventional treatment of pesticides in wastewater like photocatalytic degradation has been the focus of the attention of researchers to mitigate its impact on both humans and the environment. In this study, synthesized graphitic carbon nitride (g-C3N4) from urea is used in the photocatalytic degradation of diazinon as a photocatalyst with the addition of ferric nitrate (Fe3(NO3)3) and potassium persulfate (K2S2O8) to enhanced degradation. Graphitic carbon nitride was produced using direct calcination of urea at 550°C for 2 h. The physicochemical properties of the synthesized g-C3N4 were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), and X-ray Diffractometer (XRD). The photocatalytic degradation of diazinon was conducted under a g-C3N4/Fe(III)/persulfate system using different parameters such as catalyst loading (75, 100, and 125 mg), Fe3(NO3)3 (325, 350, and 375 mg L–1), and K2S2O8 (275, 300, and 325 mg L–1) resulting to an improved photocatalytic degradation efficiency. The physicochemical results showed a synthesized g-C3N4 that exhibits properties that are following the international standards. The results of photocatalytic degradation showed the highest degradation of g-C3N4 at 37.3%, under the parametric conditions of 125 mg g-C3N4, 325 mg L–1 of Fe3(NO3)3, and 300 mg L–1 of K2S2O8. The degradation efficiency was observed to increase as the catalyst load increases, while an increase in degradation efficiency can only be observed up to a certain value using ferric nitrate and persulfate. Overall, this study provided insight on the possible use of urea, as a source of g-C3N4 and the use of g-C3N4 as a photocatalyst using visible light as a more economic approach and cost-efficient way of handling wastewater.